Cable networks, services, and management - Toy, Mehmet (Hoboken : John Wiley & Sons Inc., 2015)
'This book will focus on residential and commercial services provided by MSOs (Multiple System Operators), the networks supporting these services, and management of networks and services. The book will cover current technologies used by MSOs and future directions pointing out areas requiring further research'--
Includes bibliographical references.
Keywords: Integrated services digital networks; Internet service providers -- Management; Home computer networks; Cable television